Adjuvant transarterial chemoembolization after radical resection contributed to the outcomes of hepatocellular carcinoma patients with high-risk factors. Issue 33 (August 2017) - Gao, Zhendong; Du, Gang; Pang, Yuguang; Fu, Zhihao; Liu, Chongzhong; Liu, Yi; Zhou, Binghai; Kong, Du; Shi, Binyao; Jiang, Zhengcheng; Jin, Bin
Abstract : Abstract: We aim to investigate the effects of postoperative adjuvant transarterial chemoembolization (TACE) on survival and recurrence in hepatocellular carcinoma (HCC) patients after radical resection. A total of 320 HCC patients underwent radical resection between January 2010 and January 2014 in Qilu Hospital, Shandong University were divided into 4 groups according to the frequency of postoperative adjuvant TACE. Patients were further stratified into subgroups (tumor diameter ⩽5 or >5 cm) with low or high risk factors for recurrence or death. A low risk factor for recurrence or death was defined as Edmondson grade I/II without microvascular invasion (MiVI), while a high risk factor was defined as Edmondson grade III/IV or with MiVI. Survival data and recurrence rates were compared using the Kaplan–Meier method. Uni- and multivariate analyses were based on the Cox proportional analysis. Compared to those received no TACE, patients underwent 2 (log-rank, χ 2 = 9.054, P = .003) or 3 (log-rank, χ 2 = 4.228, P = .04) TACE showed delayed recurrence. Patients received 2 or 3 TACE showed extended overall survival (OS) compared with the other patients. No statistical differences were found between all the disease-free survival (DFS) and OS in low-risk subgroups. In the patients of the high-risk subgroup with a tumor diameter of ⩽5, those received 2 TACE showed delayed recurrence compared with those received no TACE, and TACE (twice or thrice) can improve OS. For those of the high-risk subgroup with a tumor diameter of >5, TACE (twice or thrice) can delay recurrence and improve OS. Adjuvant TACE (twice or thrice) after radical resection is beneficial for HCC patients with poor differentiation and MiVI, especially for those with a tumor diameter of >5 cm.